PENGARUH PENGETAHUAN PRODUK DAN LITERASI KEUANGAN TERHADAP KEPUTUSAN BERTRANSAKSI PADA KSPPS GUMARANG AKBAR SYARIAH - Yudhi Kurniawan Zahari (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2021)
This study raises the title of the effect of product knowledge and financial literacy on transaction decisions at KSPPS gumarang akbar syariah. This study aims to determine the positive and significant effect partially and simultaneously product knowledge and financial literacy on transaction decisions at KSPPS Gumarang Akbar Syariah. The method used in this research is quantitative method with multiple linear regression analysis tools, this research is a field research with primary data and uses respondents as many as 50 people. Product knowledge has a positive and significant effect on transaction decisions at KSPPS Gumarang Akbar Syariah. It can be seen from the t value in the product knowledge variable of 1.805 with sig. amounted to 0.007 (p <0.05). This value is less than the significance level of 0.05. It can be stated that product knowledge has a positive and significant effect on transaction decisions at KSPPS Gumarang Akbar Syariah. Financial literacy has a positive and significant effect on transaction decisions at KSPPS Gumarang Akbar Syariah, it can be seen from the t value in the financial literacy variable of 1.503 with sig. amounted to 0.004 (p <0.05). This value is less than the significance level of 0.05. It can be stated that the financial literacy variable has a positive and significant effect on transaction decisions at KSPPS Gumarang Akbar Syariah. The contribution of product knowledge and financial literacy to transaction decisions at the KSPPS Gumarang Akbar Syariah is 0.695 or 69.05 percent, while the remaining 30.05 percent is influenced by other variants outside the research model.